Promocja w przedsiębiorstwach proekologicznych - Zaremba-Warnke, Sabina (The Promotion in Ecological Firms, 2005)
The main aims of the promotion in ecological firms are the following: creation of firms and products ecoimage and influence consumers to make them more concerned about environmental problems. Effective promotions policy have to be integrated with all marketing instruments, have to guarantee credibility and have to improve ways of communication with consumers. Those conditions have to be taken into account during the creation of all promotions instruments (advertisement, public relations, personal selling and sales promotion).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 153-167